Biological effects of allogeneic effect factor on T lymphocytes: in vitro induction of cytotoxic T lymphocytes manifesting preferential lytic activity against H-2-identical tumor cells. - Altman, A (1979)
The studies reported herein were designed to determine the effects of allogeneic effect factor (AEF), a soluble mediator generated in the course of allogeneic cell interactions, on the differentiation of cytotoxic T lymphocytes in vitro. Normal, unprimed spleen cells from various strains of mice cultured with AEF for 5 days, in the absence of any stimulator cells, developed into cytotoxic lymphocytes capable of lysing target cells in a short-term 51Cr release assay. T lymphocyte-depleted spleen cells did not become cytotoxic when cultured with AEF, and the cytotoxic cells themselves were found to be T lymphocytes. AEF-induced cytotoxic T lymphocytes preferentially lysed H-2-identical target cells. Thus, AEF, as opposed to similar "helper" factors derived from mixed lymphocyte cultures, appears to be unique in its ability to trigger normal, unprimed T lymphocytes to differentiate into cytotoxic T lymphocytes in the absence of specific antigenic stimulation.